2018
DOI: 10.1007/978-3-319-95921-4_32
|View full text |Cite
|
Sign up to set email alerts
|

Image Analysis in Light Sheet Fluorescence Microscopy Images of Transgenic Zebrafish Vascular Development

Abstract: 0000-0002-7458-5481 and Armitage, P. (2018) Image analysis in light sheet fluorescence microscopy images of transgenic zebrafish vascular development.Abstract. The zebrafish has become an established model to study vascular development and disease in vivo. However, despite it now being possible to acquire high-resolution data with state-of-the-art fluorescence microscopy, such as lightsheet microscopy, most data interpretation in pre-clinical neurovascular research relies on visual subjective judgement, rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 37 publications
(58 reference statements)
0
35
0
Order By: Relevance
“…Light-Sheet Microscopy succeeded in imaging the neural activity in two colors at 23 frames per second for over 10 min, which granted an opportunity to record the infrequent seizure crisis in mutant type, concluded that zebrafish might be used to mimic epilepsy in human [35]. Hence zebrafish became a recognized model in studying vascular development and disease in vivo [36].…”
Section: Zebrafish By Light-sheet Microscopymentioning
confidence: 99%
“…Light-Sheet Microscopy succeeded in imaging the neural activity in two colors at 23 frames per second for over 10 min, which granted an opportunity to record the infrequent seizure crisis in mutant type, concluded that zebrafish might be used to mimic epilepsy in human [35]. Hence zebrafish became a recognized model in studying vascular development and disease in vivo [36].…”
Section: Zebrafish By Light-sheet Microscopymentioning
confidence: 99%
“…Previously, Kugler et al presented methods to enhance the cerebral vasculature in LSFM data using general filtering (GF; Median Filter and Rolling ball) (Kugler et al, 2018) and enhancement utilizing the Hessian matrix with the assumption of local vessel tubularity, based on the filter proposed by Sato et al (Kugler et al, 2019;Sato et al, 1997). This was further complemented by investigation of different segmentation approaches, which were readily implemented in the Fiji image analysis framework (Schindelin et al, 2012), but no validation of the suggested approach was performed.…”
Section: Previous Work Aiming To Quantify the Zebrafish Cerebral Vascmentioning
confidence: 99%
“…(i) Dataset with controlled decrease of vascular contrast-to-noise ratio (CNR) by decrease of laser power during repeated acquisition (Kugler et al, 2018) (laser power (LP) 1.2%, 0.8% and 0.4%; exposure 30ms for all; 4dpf; n=10 embryos from 2 experimental repeats). Augmented data were produced from LP 1.2% by addition of Gaussian noise with mean of zero and standard deviation of 50 using Fiji (Schindelin et al, 2012).…”
Section: Transgenic Zebrafishmentioning
confidence: 99%
“…An estimate of background noise was obtained by measuring the standard deviation (σ) in a region of interest placed outside of the fish. CNR (Equation (1)) was calculated, as below: Sample motion artefact assessment and correction were conducted as described in [13]. Two approaches for vascular enhancement were evaluated.…”
Section: Contrast-to-noise Ratio (Cnr)mentioning
confidence: 99%
“…Two approaches for vascular enhancement were evaluated. The first utilised an optimised general filtering approach for image artefact and noise reduction [13], while the second was based around using image gradient information for enhancing tubular structures. Both methods were performed on data from the Tg(kdrl:HRAS-mCherry) s916 line after 3D slice-by-slice motion correction as follows:…”
Section: Contrast-to-noise Ratio (Cnr)mentioning
confidence: 99%